PERAN AKTIF ORANG TUA DALAM MELAKUKAN UPAYA PREVENTIF KESEHATAN GIGI ANAK DI MASA PANDEMIC COVID-19 - Erwin Erwin (LP2M Universitas Ibrahimy, 2022)
Children's dental health is an important part of body health to support child growth and development. The good dental health of children will support the process of chewing food, communication and encourage children to be confident in socializing. Children's teeth are at risk of decay compared to adult teeth because of the clinical condition of children's teeth and the behavior of children who are not yet independent. Therefore, parents must be involved in preventive efforts for children's dental health. The community service method uses active participating targets, the targets in this activity are parents and grade 1 students of Teladan Al Hidayah Islamic Elementary School, East Cilandak, the implementation period of the activity is from July to August 2021, the form of activities carried out are counseling and mentoring. The results of the activity showed that the extension activities were carried out well, the participants listened carefully and enthusiastically. Then, the mentoring activities took place well, intensively, and in an orderly manner carried out in small groups so that each participant was able to practice the preventive efforts that had been trained.